EFFECTS OF AEROBIC AND PROGRESSIVE RESISTANCE EXERCISE TRAININGS ON GROSS MOTOR SKILLS AND PHYSIOLOGICAL PARAMETERS OF PRIMARY SCHOOL PUPILS IN IBADAN, NIGERIA (2012)
Gross Motor Skills (GMSs) ability in children begins to emerge and mature during the preschool and elementary years. Lack of Aerobic Exercise (AE) and Progressive Resistance Exercise (PRE) may impede qualitative patterns of GMSs and expose pupils to unhealthy lifestyle in future. Studies are available on the utilisation of AE and PRE to improve physical-physiological profiles of secondary school students in Nigeria, but gross motor skills and physiological parameters of primary school pupils have not been addressed. The study, therefore, investigated the effects of AE and PRE trainings on the GMSs, Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), Heart Rate (HR), Percent Body Fat (%BF) and Body Mass Index (BMI) of primary school pupils in Ibadan, Nigeria. The pretest-posttest, control group experimental research design was adopted. Participants were 180 (93 from public and 87 from private schools) pupils purposively drawn from primaries 3, 4 and 5 of each of the two public and private primary schools used. Systematic random sampling technique was used to assign the participants into experimental groups (AE, PRE) and control group. Each of the experimental groups was exposed to a 12-week interval training programme. Pretest-posttest data were collected using Test of Gross Motor Development (TGMD-2) (r=0.91), height meter (r=0.99), weighing scale (r=0.96), Sphygmomanometer (r=0.97), Stethoscope (r=0.98) and Skin-fold Caliper (r=0.89). Three research questions were answered and six hypotheses tested at 0.05 level of significance. Data were analysed using analysis of covariance, Scheffe post hoc test and t-test. Primary school pupils had normal systolic and diastolic blood pressure and heart rate but were underfat, underweight and very poor in GMSs levels. There were significant effects of treatments on GMSs (F (3,176) = 257.75, p<0.05), SBP (F (3,176) = 6.86, p<0.05), heart rate (F (3,176) = 9.57, p<0.05) and BMI (F (3,176) = 6.375, p<0.05). However, there was no significant effect of treatments between the GMSs of public and private primary schools pupils as well as between the GMSs of boys and girls in primary schools. Scheffe post hoc test shows that there was a significant mean difference in GMSs among the three groups (PRE and AE, = 6.4; PRE and control, = 20.0). It further showed that the significant mean difference in SPB was between PRE and control ( = 8.0); HR was between AE and control ( = 8.7); BMI was between PRE and control ( = 1.27). AE and PRE enhanced GMSs, SBP, DBP, HR, %BF and BMI in primary school pupils in Nigeria. Therefore AE and PRE should be emphasised in the physical education programme of primary school pupils in order to improve qualitative GMSs, body fat and body weight.